2022
DOI: 10.1371/journal.ppat.1010283
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinase Ire1 has a Hac1-independent essential role in iron uptake and virulence of Candida albicans

Abstract: Protein kinases play central roles in virtually all signaling pathways that enable organisms to adapt to their environment. Microbial pathogens must cope with severely restricted iron availability in mammalian hosts to invade and establish themselves within infected tissues. To uncover protein kinase signaling pathways that are involved in the adaptation of the pathogenic yeast Candida albicans to iron limitation, we generated a comprehensive protein kinase deletion mutant library of a wild-type strain. Screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…C. albicans Casky1D andCasky2D (orf19.35) deletion mutants were taken from the existent mutant library of non-essential uncharacterized predicted protein kinases (Ramıŕez-Zavala et al, 2022). All other C. albicans deletion mutants and complemented strains were constructed as described previously (Ramıŕez-Zavala et al, 2017).…”
Section: Candida Albicans Strain Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. albicans Casky1D andCasky2D (orf19.35) deletion mutants were taken from the existent mutant library of non-essential uncharacterized predicted protein kinases (Ramıŕez-Zavala et al, 2022). All other C. albicans deletion mutants and complemented strains were constructed as described previously (Ramıŕez-Zavala et al, 2017).…”
Section: Candida Albicans Strain Constructionmentioning
confidence: 99%
“…To test whether CgSky1, CaSky1, and CaSky2 are involved in similar cellular functions we generated C. glabrata mutant strains lacking SKY1 (Cgsky1D) and C. albicans strains lacking both SKY1 and SKY2 (Casky1D Casky2D). In addition, we used available C. albicans Casky1D and Casky2D (orf19.35) mutants (Ramıŕez-Zavala et al, 2022). As a control we used the S. cerevisiae BY4741 wild-type strain and a sky1D mutant (Scsky1D).…”
Section: Sky1 and Sky2 Are The Sole Predicted Sr-like Protein Kinases...mentioning
confidence: 99%
“…Additionally, this work contributes to the growing appreciation for Hac1-independent mechanisms of Ire1 function in pathogenic fungi. 46 , 47 , 48 , 49 While previous reports have observed that both the overexpression and depletion of the stress response regulator Hsf1 induces filamentation in the liquid medium, 50 to our knowledge this is the first example of a protein for which overexpression and depletion lead to comparable phenotypes in distinct media states.…”
Section: Discussionmentioning
confidence: 86%
“… 13 , 54 , 55 , 56 , 57 , 58 With Ire1, there has been growing interest in its potential as a therapeutic target as it is critical for growth under host-relevant stress conditions, including elevated temperature and iron-limitation. 28 , 49 Furthermore, this kinase is reported to have a key role in biofilm formation in vivo , as well as for pathogenicity in a mouse model of systemic infection. 28 , 49 In the pharmaceutical sector, Ire1 has become an attractive therapeutic target for the treatment of several human diseases, including cancer, as illustrated by ORIN1001, a selective inhibitor of Ire1 that entered clinical trials for patients with advanced solid tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation